Avian assemblages in bamboo and non-bamboo habitats in a tropical rainforest - Rother, Débora Cristina [UNESP]; Alves, Kaizer José Ferreira; Pizo, Marco Aurélio [UNESP] (Taylor & Francis, 2013)
Some species of bird are closely associated with bamboos (bamboo specialists) but community-wide studies comparing the avian assemblages in bamboo and non-bamboo habitats are lacking. Using point counts, we compared the species richness, abundance and composition of the avian assemblages in bamboo and non-bamboo habitats in the Brazilian Atlantic forest. Apart from considering bamboo specialists and non-specialist species, we contrasted birds from different categories of forest dependence, forest strata and diet. We recorded a total of 81 species of birds (74 in bamboo, 55 in non-bamboo habitats), including 15 bamboo specialists. Species richness was greater in bamboo habitats in all categories of diet and forest dependence. Bamboo and non-bamboo habitats had a similar number of canopy species, but bamboo habitats had a greater number of non-canopy species. The abundance of the whole avian community or of each of the dietary categories did not differ between habitats. The overall species composition differed between habitats, with a more homogeneous composition in non-bamboo habitats. A great number of species use bamboo habitats, even if they are not bamboo specialists. The initial expansion of bamboos, forming discrete patches of bamboo within mature forest, represents an intermediate-level disturbance that enhances forest heterogeneity and promotes the diversity of avian communities. © BirdLife Australia 2013.
Keywords: Atlantic forest; Brazil; diet; forest dependence; forest strata; intermediate-disturbance hypotheses; abundance; avifauna; bamboo; bird; habitat fragmentation; heterogeneity; rainforest; specialist; species diversity; species richness; tropical forest; Atlantic Forest